US trade wars in the twenty‐first century with emerging countries: Make America and its partners lose again. (5th September 2018) - Bouët, Antoine; Laborde, David
Abstract: In a context of rising protectionist rhetoric, this paper looks at the potential impact of trade wars initiated by a change in US trade policies. We use a static multicountry, multisector general equilibrium model to evaluate six modalities of three potential trade wars—for a total of 18 scenarios—between the USA and China, between the USA and Mexico, and a combination of the two previous conflicts. In each case, we evaluate various forms of trade retaliation by the US partner(s): the same level of import duty as the one imposed by the USA, an import duty that minimises welfare loss, a duty that minimises terms‐of‐trade deterioration, a duty that generates the same amount of collected revenue, and finally a Nash equilibrium. We conclude that there is no scenario in which the US government augments its domestic welfare or GDP. There may be sectoral gains in value added in the USA, but they are small and to the detriment of other sectors. While losses for China are relatively small, potential losses for the Mexican economy are significant. There are also free riders of these trade wars. Finally, the way in which trade retaliations are designed matters greatly.